Recommendations for the Advancement of Health Tourism in the Kurdistan Region Using Information Technology - غثىان غصام غبد امِاذد; امىدرس الدکجِر ذسان غثىان ورىد ثِفيق (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The medial tourism is one of the branches of the economy, which generates a tangible presence for many of the neighboring countries in general and the region of Kurdistan in particular, after being paid attention to and development. The researchers seeks to provide a knowledge about this tourism and strategies to promote it in the Kurdistan region. The purpose of this study is to identify the nature of medical tourism and its components in neighboring countries and provide a model to inform customers in this tourism through the use of marketing information technologies. The researchers concluded that the development of the medical tourism sector in the Kurdistan region is through the adoption of a marketing information system that rationalizes the decisions related to this sector, through the construction of a marketing database in an interactive form among the health institutions and their beneficiaries. So that they conclude that , Quality in the health field for the purpose of upgrading health services to world-class and developing medical tourism in the Region, providing a regulatory body on the quality of medical services and linking the quality of services with price control activities for various operations.